Corporate Social Responsibility: Benefit(s) to Company and Society Case of Vodafone Ghana Limited - Mantey, Nicholas (Advances in Social Sciences Research Journal, 2024)
This project explores the principles of corporate social responsibility (CSR) and its benefits to both companies and society. The case study conducted on Vodafone Ghana provides a practical illustration of implementing CSR practices. The primary objective of this study is to review the effect of CSR initiatives on Vodafone Ghana’s performance and its contribution to society. The research methodology employed in this study involves analyzing relevant literature, collecting primary data through interviews and surveys, and conducting a comprehensive review of Vodafone Ghana’s CSR activities. The findings indicate that Vodafone Ghana’s CSR initiatives have positively influenced its reputation, brand image, and customer loyalty. The research findings, the study was that implementing CSR practices can bring about tangible benefits to both companies and society. It enhances a company’s competitiveness, strengthens stakeholder relationships, and contributes to sustainable development. Overall, this project highlights the significance of CSR in fostering a positive relationship between companies and society, using Vodafone Ghana as a case study. It offers insights for organizations leveraging CSR practices for sustainable growth and societal well-being.